The Investigation of Volkswagen's Entry Strategy in China's Car Market - WEN, XIAOFENG (2007)
China is one of the most attractive investment destinations for the world investors, now almost all the world car-manufacturing giants have launched their factories in this country, making huge efforts to explore their market share. And it has one of the world's largest car markets, in the past few years sales have grown forty to sixty percent annually. The favorable macro-environment and policy environment has enabled China's car industry grew fast and steadily. Volkswagen (hereafter VW) is one of the earliest investors and the biggest foreign car maker in China, its entry and development strategy is very successful, now it controls over 30% of the China's car market. This piece of study analyses the international strategy of VW, and focuses on its investment strategy in China, particular attention was paid on its selection of entry modes when it entered Chinese market, the objective was to find out which particular modes did VW use to enter Chinese market and what are the rationales behind such choice. It was found that it is the macro environment (political, economic, social and technological) and micro environment (threat from five forces) of China lends itself to a particular entry mode: joint venture. It also presented the challenges and directions of the company in its future development in China